2022
DOI: 10.1002/mus.27506
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of diagnostic delay in Guillain‐Barré syndrome in a UK tertiary center

Abstract: Introduction/Aims: Understanding the potential causes and consequences of diagnostic delay in Guillain-Barré syndrome (GBS) could improve quality of care and outcomes. We aimed to determine these causes and consequences in our cohort of patients with GBS.Methods: We retrospectively reviewed records of subjects with GBS, admitted to our center at University Hospitals Birmingham, UK, between January 2005 and December 2020. We evaluated time to diagnosis from presentation, factors associated with diagnostic delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Interestingly, we observed the delay between GBS onset and hospital admission was longer in pGBS in comparison with npGBS, i.e., 9 days vs 6 days, and we wondered whether this increased delay might play a role in our findings. However, a recent retrospective study showed there was no correlation between GBS diagnostic delay and ICU admission, mechanical ventilation, and inpatient mortality [ 11 ]. We also wondered whether pregnancy-related physiological changes might explain the difference between pGBS and npGBS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed the delay between GBS onset and hospital admission was longer in pGBS in comparison with npGBS, i.e., 9 days vs 6 days, and we wondered whether this increased delay might play a role in our findings. However, a recent retrospective study showed there was no correlation between GBS diagnostic delay and ICU admission, mechanical ventilation, and inpatient mortality [ 11 ]. We also wondered whether pregnancy-related physiological changes might explain the difference between pGBS and npGBS.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt treatment in combination with adequate physical therapy thus proved to be an appropriate treatment course for this patient. In considering atypical variants of GBS, prompt treatment is of even greater importance since ambiguity surrounding the correct diagnosis may delay treatment and therefore permit further disease progression [ 12 ]. Hence, this case also demonstrates the importance of early recognition of both classic and atypical clinical patterns in order to appropriately diagnose and treat patients in a timely manner so as to prevent complications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the case of rare variants such as the pharyngeal-cervical-brachial (PCB) variant or acute bulbar palsy (ABP)-plus syndrome, prominent bulbar palsy may be the first or sole clinical manifestation [ 5 , 6 ]. Patient-specific factors, such as age >60 years, pre-existing medical diseases, and atypical clinical presentations, have been recognized as factors significantly associated with both delayed diagnosis and increased mortality in cases of GBS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%